Climate ultrastructure and aquatic community response to Heinrich Stadials (HS5a-HS1) in the continental northern Neotropics. (1st October 2018) - Cohuo, Sergio; Macario-González, Laura; Pérez, Liseth; Sylvestre, Florence; Paillès, Christine; Curtis, Jason H.; Kutterolf, Steffen; Wojewódka, Marta; Zawisza, Edyta; Szeroczyńska, Krystyna; Schwalb, Antje
Abstract: We reconstruct environmental conditions of the period 53-14 kyr BP in the continental northern Neotropical region. We evaluate in detail the magnitude of climatic fluctuations and their effects on aquatic communities during six Heinrich Stadials (HS1-HS5a), using sediments from Lake Petén Itzá, Guatemala, and a multiproxy approach. In Lake Petén Itzá typical Heinrich Stadials (HSs) are recorded in sediments as alternations of gypsum and clay, and abrupt changes in magnetic susceptibility, CaCO3 and biological compositions. This suggests that HSs were periods of hydrological unbalance, characterized by dry spells, punctuating the predominant humid conditions characterizing the period 53-14 kyr BP. The ultrastructure of HSs allows us to identify four different types of climatic conditions associated to HSs: 1) prevailing dry conditions but changing to humid (HS5, HS3); 2) predominantly humid conditions but changing to arid (HS2); 3) fluctuating humid-dry-humid (HS4, HS1); and 4) arid with high lake water conductivity (HS5a). The continuous presence of tropical ostracode species during HSs suggests that lake water temperatures were not drastically lowered. Ostracode-based transfer functions indicate that during HSs, epilimnetic water temperatures decreased by 1–3 °C compared to mean modern temperatures. Lake solute composition and conductivity were strongly affected by HSs. During HS5a and HS1 we estimate conductivity values > 800 μS cm −1 . Diversity indices show significant differences (F5, 70  = 3.74, p  = 0.004) of ostracode species composition among HSs. Highest diversities occurred during HS5a, HS4 and HS1, which display greater climatic alterations than the other HSs. Fluctuating climates seem to have exerted positive effects on diversity of aquatic communities by producing an increase in habitat heterogeneity. Highlights: Evaluation of environmental variability induced by Heinrich Stadials (HS5a-HS1) in continental northern Neotropical region. Multiproxy evidence reveals mild temperature decreases and drastic fluctuations in precipitation during HSs. Ultrastructure of HSs suggests individual environmental response of each Stadial making them contrasting from each other. Most drastic climate changes induced by HSs exerted positive effects on diversity of aquatic communities.